1984
DOI: 10.1080/00365521.1984.12005812
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Asymptomatic Recurrences of Duodenal Ulcer

Abstract: Thirty-six patients in whom an asymptomatic duodenal ulcer had been detected endoscopically were followed up clinically and endoscopically during the following months. Ten of the patients were receiving either no treatment or placebo, and 26 patients were receiving maintenance treatment with either 150 mg ranitidine or 400 mg cimetidine at night. Treatment remained unchanged during the follow-up period. The cumulative annual rate of spontaneous healing was approximately one quarter, whether or not patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Follow-up studies of asymptomatic ulcers in patients receiving maintenance therapy have demonstrated that such ulcers rarely cause clinical problems-each month during continued maintenance therapy approximately 33% reheal, 61% remain unchanged, and only 6 % give rise to symptoms (35). Similar findings have been reported previously (37) and were also observed in an unreported maintenance study with full-dose ranitidine (referred to above) in which all patients were endoscopically examined after 2, 4, 8, 12, and 16 weeks of maintenance therapy. These findings suggest that it is unnecessary t o attempt to diagnose and reheal asymptomatic ulcers in patients receiving maintenance therapy with H2receptor antagonists.…”
Section: Asymptomatic Ulcer Recurrencessupporting
confidence: 65%
“…Follow-up studies of asymptomatic ulcers in patients receiving maintenance therapy have demonstrated that such ulcers rarely cause clinical problems-each month during continued maintenance therapy approximately 33% reheal, 61% remain unchanged, and only 6 % give rise to symptoms (35). Similar findings have been reported previously (37) and were also observed in an unreported maintenance study with full-dose ranitidine (referred to above) in which all patients were endoscopically examined after 2, 4, 8, 12, and 16 weeks of maintenance therapy. These findings suggest that it is unnecessary t o attempt to diagnose and reheal asymptomatic ulcers in patients receiving maintenance therapy with H2receptor antagonists.…”
Section: Asymptomatic Ulcer Recurrencessupporting
confidence: 65%
“…Clinical data (8) indicate that asymptomatic relapses during active maintenance therapy are clinically benign, since such ulcers rarely give rise to complications. Therefore, all further evaluation of the data has been based only on ulcer recurrences with typical ulcer symptoms or complications of the disease.…”
Section: Life-table Analysismentioning
confidence: 96%
“…Early studies before the discovery of H pylori and proton-pump inhibitor reported relapse rates of up to 74% during a 12-month follow-up period. 73,74 Approximately 25% to 40% of the ulcer recurrences were asymptomatic, 75,76 whereas others may present with rebleeding. 77,78 Definitive treatment and preventive measures are required to reduce ulcer recurrence and its complications.…”
Section: Therapeutic Management Of Recurrent Ulcer Diseasementioning
confidence: 99%
“…[73][74][75][76] It is, therefore, important to ensure complete eradication of the bacterium. An early study comparing eradication therapy (bismuth, metronidazole, and tetracycline) with acid-suppression therapy (omeprazole) showed similar rates of gastric ulcer healing but a significantly lower rate of ulcer recurrence in the eradication group (4.5% vs 53.2%, P<.01).…”
Section: Helicobacter Pylori Ulcersmentioning
confidence: 99%